Pengaruh Aromaterapi Jahe dan Akupresur pada Titik Perikardium 6 terhadap Skor Mual Muntah pada Ibu Hamil Trimester I dengan Emesis Gravidarum - Faturanti, Risa Ayu; Kartilah, Tetet; Februanti, Sofia; Nurhayati, Tetik (PSIK FKKMK UGM, 2025)
Background: Pregnant women often experience nausea, vomiting, and abdominal pain (emesis gravidarum) in the first trimester, which can affect their activity and health. Aromatherapy and acupressure are two safe methods that have few side effects. Research on the use of ginger aromatherapy and P6 acupressure to reduce nausea and vomiting in pregnant women at the Cibeureum Health Center has never been conducted. Objective: To examine the effectiveness of Ginger aromatherapy and P6 acupressure combination in reducing emesis gravidarum among pregnant women who experience emesis gravidarum in their first trimester. Methods: The type of research was a quasi experiment with a nonequivalent (pretest and posttest) with control group design. A total of 26 participants were selected using simple random sampling technique from a total of 32 first-trimester pregnant women for this research. The intervention group and the control group were both given Ginger aromatherapy. The intervention group then received additional acupressure at the P6 point. To measure symptoms, the PUQE-24 questionnaire was used. Before the statistical test was carried out, the data collected was tested for normality and homogeneity of data. Then, data were analyzed using independent t-tests, Wilcoxon, and Mann Whitney. Results: There was a statistically significant decrease in emesis gravidarum symptoms score from 9,54 to 5,08 occurred in the intervention group, while in the control group it also decreased from 10,62 to 9,00. In both groups, there was a significant decrease in nausea and vomiting scores (p=0,001 and p=0,003) The median values of the difference in nausea and vomiting scores in the intervention group were 4 (3-8) and in the control group 2 (1-4). From the result of the Mann Whitney test, the value of p = 0,000 was obtained. Conclusion: The combination therapy of Ginger aromatherapy and P6 point acupressure may reduce the symptoms of emesis gravidarum in pregnant women in the first trimester.INTISARILatar belakang: Wanita hamil sering mengalami mual, muntah, dan nyeri perut (emesis gravidarum) pada trimester pertama, yang dapat memengaruhi aktivitas dan kesehatan mereka. Aromaterapi dan akupresur adalah dua metode aman yang memiliki sedikit efek samping. Penelitian tentang penggunaan aromaterapi Jahe dan akupresur P6 untuk mengurangi mual dan muntah pada ibu hamil di Puskesmas Cibeureum belum pernah dilakukan. Tujuan: Mengkaji efektivitas kombinasi aromaterapi Jahe dan akupresur P6 dalam mengurangi mual muntah wanita hamil yang mengalami emesis gravidarum pada trimester pertama. Metode: Jenis penelitian adalah quasi experiment with a nonequivalent (pretest and posttest) dengan control group design. Sebanyak 26 partisipan dipilih menggunakan teknik simple random sampling dari total 32 wanita hamil trimester pertama untuk penelitian ini. Kelompok intervensi dan kelompok kontrol sama-sama diberikan aromaterapi Jahe, kelompok intervensi selanjutnya menerima tambahan akupresur pada titik P6. Untuk mengukur gejala, digunakan kuesioner PUQE-24. Sebelum dilakukan uji statistik, data yang terkumpul dilakukan uji normalitas dan homogenitas data. Data dianalisis menggunakan uji t independen, Wilcoxon, dan Mann Whitney. Hasil: Terdapat penurunan skor gejala emesis gravidarum yang signifikan secara statistik dari 9,54 menjadi 5,08 pada kelompok intervensi. Sementara itu, pada kelompok kontrol juga turun dari 10,62 menjadi 9,00. Pada kedua kelompok terjadi penurunan yang signifikan terhadap skor mual dan muntah (p=0,001 dan p=0,003). Nilai median selisih skor mual muntah pada kelompok intervensi sebesar 4 (3-8) dan pada kelompok kontrol 2 (1-4). Dari hasil uji Mann Whitney didapatkan nilai p = 0,000. Simpulan: Gabungan terapi aromaterapi Jahe dan akupresur titik P6 dapat menurunkan gejala emesis gravidarum pada ibu hamil di trimester I.